APLIKASI MULSA ORGANIK ALANG-ALANG DANPUPUK KANDANG AYAMTERHADAP PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L.) - Manurung, Desi K; Armaini, Armaini; Dini, Isna Rahma (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to determine the effect and get the best combination of organic mulch congongrass and chicken manure on the growth and production of onion (Allium ascalonicum L.) The research was conducted in experimental garden of the Faculty of Agriculture, University of Riau on Campus Bina widya Km 12.5 Kelurahan Simpang Baru Kecamatan Tampan Pekanbaru from April to June 2017. The research was conducted in a randomized complete design (RAL). The treatment was done by doing a combination between organic mulch with chicken manure. The parameters in this observation were plant height, number of leaves, number of tubers, percentage of tubers, tuber weight and tuber weight of storage. The results obtained were analyzed statistically using variance analysis and continued with a 5% DNMRT advanced test. The results showed that combination treatment without organic mulch congongrass and chicken manure 13,890 kg/ha can increase plant height, leaf number, tuber weight, fresh weight of tuber and tuber weight is saving but no effect on the number of onion crop tubers. Combination treatment without the application of organic mulch congongrass and chicken manure 13,890 kg/ha can increase fresh weight of onion plant as much as 112,74% and save weight of onion plant as much as 250% compared with mulching and without chicken manure. Keyword: Combination, organic mulch congongrass, chicken manure